Growth Rate of Rhizophora Mucronata Seedlings in Coastal Areas of Central Java - Eva Widayanti; Teguh Firmansyah (Research Horizon, 2022)
Rhizophora mucronata is a type of mangrove from the Rhizophora family that can have high adaptability to an environment. The seed nursery process can be carried out by several methods, including the wetland and dry land methods. This study aims to determine the growth of mangroves. The material used in this fieldwork practice is to see how the techniques and methods of mangrove nurseries (Rhizophora mucronata) are used by the NGO Biota Foundation. The methods include preparing maintenance by embedding propagules in polybags using the wetland method in tidal areas. The results show the growth of Rhizophora mucronata mangrove from the pericarps root size, reaching 0.1 mm at four weeks.